Accuracy of data analysis on university student's major subject and job sector prediction using KNN and decision tree algorithm - Ahmed, Istear; Karmakar, Tushar; Anadi, Iffat Sumaita; Azad, MD.Shahriar; Sharif, Faiza Ibnat (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.